2016
DOI: 10.19126/suje.17778
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of T-STEM Designation On Charter Schools: A Longitudinal Examination Of Students’ Mathematics Achievement

Abstract: STEM interested students and graduates shape the future of a country. However, in the U.S., the number of STEM graduates was not sufficient; therefore, to increase this number, STEM school designation started. The number of STEM schools has been increasing and Texas was one of the states showing growth over time. STEM schools in Texas (T-STEM) were converted from different schools by specific procedures. The highest number of T-STEM conversion was from charter schools. The effectiveness of T-STEM charter schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous research has focused on high schools, examining whether students at STEM Schools perform better than their peers at non-STEM schools. While some studies found improved math and science scores (Erdogan & Stuessy, 2015a, 2015bNavruz et al, 2014), others found no difference (Bicer et al, 2014;Hansen, 2014;Means et al, 2016Means et al, , 2017Oner et al, 2016;Weis et al, 2015), or even lower scores (Glennie et al, 2016). Additionally, controlling for socioeconomic status (SES) and ethnicity dampens positive results (Öner et al, 2014;Wiswall et al, 2014).…”
Section: Impact Of Stem Schools On Studentsmentioning
confidence: 99%
“…Previous research has focused on high schools, examining whether students at STEM Schools perform better than their peers at non-STEM schools. While some studies found improved math and science scores (Erdogan & Stuessy, 2015a, 2015bNavruz et al, 2014), others found no difference (Bicer et al, 2014;Hansen, 2014;Means et al, 2016Means et al, , 2017Oner et al, 2016;Weis et al, 2015), or even lower scores (Glennie et al, 2016). Additionally, controlling for socioeconomic status (SES) and ethnicity dampens positive results (Öner et al, 2014;Wiswall et al, 2014).…”
Section: Impact Of Stem Schools On Studentsmentioning
confidence: 99%